ANALYSIS OF THE SCENARIO OF MIGRATION IN ASSAM - Julfair Mazid Kazi (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Birth, death and migration are the demographic components which are considered as the determining elements of population change. Along with birth and death, migration holds an important position in the concept of population change. Balanced growth and development are necessary for the development and welfare of the nation. But hardly have we found a nation which has all round development. Regional imbalances and underdevelopment are the focal points which mainly lead people to move from one region to the other. People thus tend to move to the areas which have better opportunities in store for them. Migration can be internal and external. Internal migration is when the movement takes place within the country whereas the external migration is when movement of individuals takes place between two different countries. In this paper we try to analyze the secondary data related to the migration scenario in Assam.